COMPARISON OF INVESTMENT AGREEMENT LEGALITY USING BITCOIN MEDIA IN INDONESIA - Evryansyah, Muhammad Bilal; Wahjuningati, Edi (jfpublisher, 2023)
There has been a huge growth in the value of bitcoin in Indonesia, especially during late 2017. Many people are interested and aware of this phenomenon related to Bitcoin that operates only as a digital system and has no physical existence. This research will further discuss Bitcoin as an investment agreement object. This research uses a normative legal research method with a conceptual approach that refers to the law. This research aims to determine and analyze the comparison of the validity of investment agreements that use Bitcoin as an investment object in several countries. In addition, to find out and analyze the legal protection of the parties who make Bitcoin buying and selling transactions using the Indodax website facility under Indonesian law. The results of this research indicate that there are differences of legal basis to regulate Bitcoin transaction agreements between El Salvador and Indonesia. In El Salvador, the Bitcoin Law is set as the legal basis for regulating Bitcoin transaction agreements. Whereas in Indonesia, the legal basis for regulating Bitcoin transaction agreements is the Commodity Futures Trading Supervisory Agency Regulation No. 5/2019 concerning Technical Provisions for the Implementation of the Crypto Asset Physical Market on the Futures Exchange.